2019
DOI: 10.1111/ggi.13787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of walking on depression prevalence for diabetes using information communication technology: Prospective study

Abstract: Aim This study aimed to evaluate the prevention of diabetic depression and its impact on medical costs through the implementation of a step count monitoring system using information and communication technology. Methods This study carried out a longitudinal analysis of a prospective cohort. A total of 296 participants were enrolled in the intervention group and 882 participants in the control group. The participants in the intervention group were provided with pedometers, which each participant was asked to sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We used a system 14,15) that we had developed to obtain the step count for each participant. Participants were able to record their step count on an electronic cloud by having their pedometers read by terminals installed at 27 locations across the city.…”
Section: Step Count Data Collection Systemmentioning
confidence: 99%
“…We used a system 14,15) that we had developed to obtain the step count for each participant. Participants were able to record their step count on an electronic cloud by having their pedometers read by terminals installed at 27 locations across the city.…”
Section: Step Count Data Collection Systemmentioning
confidence: 99%
“…17 Similarly, men and women with hearing impairment and a history of communication difficulties at home are at risk for depression in adulthood. 18 Effective communication can improve people's moods and reduce symptoms of anxiety and depression, [19][20][21][22] and one study demonstrated the commitment of their orthopaedic and trauma surgery specialty from government to overcome the pandemic by providing competent personnel as well as close cooperation with hospital administration and other departments. 23 However, to prevent new coronavirus infections, medical staff members need to wear protective clothing, masks, and protective screens.…”
Section: Introductionmentioning
confidence: 99%
“…2 Based on available evidence, ICT can improve healthcare outcomes and reduce associated costs. [3][4][5] The growing use of ICT, through telenursing and telehealth, is a promising advance in the provision of health services that minimise health concerns. 6 Telehealth or e-health, is the general use of ICT to provide health-related services to patients from a distance.…”
mentioning
confidence: 99%